Data Driven Agriculture: Needs Assessment and Profiling of Farmers in Bangkal and Palili - Edessa Flordeliz; Abigail G. Abuan (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aligns with multiple United Nations Sustainable Development Goals, particularly SDG 1 (No Poverty), SDG 2 (Zero Hunger), and SDG 4 (Quality Education), by examining agricultural practices and training needs in rural communities. The research focused on farmers from two barangays adjacent to BPSU Abucay Campus: Bangkal (95 respondents) and Palili (29 respondents). The investigation assessed three key areas: socio-demographic characteristics, farming profiles, and training needs using the Borich model. Contributing to SDG 1 and SDG 2, the findings revealed that while most respondents owned their farmland, their household income was derived from multiple sources rather than farming alone, indicating the need for sustainable agricultural practices to improve farm productivity and income. In terms of agricultural practices, the majority of farmers employed a mixed approach, utilizing both organic and commercial fertilizers. The study also found diverse perspectives and varying approaches to farming activities among the respondents. Addressing SDG 4's goal of quality education and lifelong learning, the training needs assessment yielded an interesting paradox: while the farmers demonstrated existing knowledge and capabilities in various agricultural topics, they generally perceived the proposed training subjects as low priority. This disconnect between capability and perceived importance suggests a need to reevaluate the approach to agricultural training programs in these communities to better support sustainable farming practices and improved livelihoods.